2020
DOI: 10.1155/2020/4216160
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Aboveground Biomass of an Evergreen Broadleaf Forest in Xuan Lien Nature Reserve, Thanh Hoa, Vietnam, Using SPOT-6 Data and the Random Forest Algorithm

Abstract: Forest biomass is an important ecological indicator for the sustainable management of forests. The aim of this study was to estimate forest aboveground biomass (AGB) by integrating SPOT-6 data with field-based measurements using the random forest (RF) algorithm. In total, 52 remote sensing variables, including spectral bands, vegetation indices, topography data, and textures, were extracted from SPOT-6 images to predict the forest AGB of Xuan Lien Nature Reserve, Vietnam. To determine the optimal predictor var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 54 publications
2
6
0
1
Order By: Relevance
“…Studies that used satellite remote sensing data for AGB prediction highlighted a common drawback in terms of data saturation and low prediction precision [18], [26], [71]. Our study analyzed multiple models for different datasets and found two effective ways to reduce the bias and data saturation.…”
Section: Discussionmentioning
confidence: 91%
“…Studies that used satellite remote sensing data for AGB prediction highlighted a common drawback in terms of data saturation and low prediction precision [18], [26], [71]. Our study analyzed multiple models for different datasets and found two effective ways to reduce the bias and data saturation.…”
Section: Discussionmentioning
confidence: 91%
“…The bagging approach is based on the premise that combining learning models improves the final result. Several studies have investigated the RF algorithm's potential for random agricultural forests [123,124]. The advantages of using this approach include resolving vector collinearity issues, often encountered while using traditional LR models.…”
Section: Support Vector Machine (Svm)mentioning
confidence: 99%
“…Similarly, the relationship between forest attributes (e.g., forest structure, tree species diversity and functional traits) and AGC storage is less well studied (Con et al, 2013). Previous works in this ecoregion have only developed sets of allometric equations to improve estimations of tree aboveground biomass (AGB) (Huy et al, 2016a;2016b) and remote sensing technology to estimate AGC storage (Luong et al, 2015;Avitabile et al, 2016;Nguyen & Kappas, 2020).…”
Section: Introductionmentioning
confidence: 99%